The Philippines on debt row - Beja, Edsel L. (2009)
Heavy indebtedness and debt service payments, indicated by debt magnitudes and shares to national budgets, revenues, or outputs, mean that spending for public infrastructure and basic service is crowded out, even as they entail more borrowings in order to timely meet debt obligations. The failure to reduce indebtedness, improve national revenues, and raise incomes has contributed to the economic decrepitude of the Philippines. Debt relief is necessary to pull the country out of such a state of affairs.
Keywords: Public debts -- Philippines; Debt management